Pengaruh Kinerja Perusahaan Terhadap Nilai Perusahaan Dengan Kebijakan Deviden Sebagai Variabel Intervening Perusahaan Manufaktur (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bei) - Puspita Sari, Yusfrina Apri; Titisari, Kartika Hendra; Pawenang, Supawi (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to evaluate the extent to which corporate performance influences firm value, with dividend policy serving as an intervening variable. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Corporate performance is assessed using three main indicators: liquidity (measured by the current ratio), profitability (measured by return on assets), and leverage (measured by the debt to equity ratio). Firm value is proxied by Price to Book Value (PBV), while dividend policy is measured by the Dividend Payout Ratio (DPR). A quantitative approach is employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The results indicate that liquidity, profitability, and leverage do not have a direct significant effect on firm value. However, both profitability and leverage significantly influence dividend policy. Despite this, dividend policy does not mediate the relationship between corporate performance and firm value. These findings suggest that, in the context of Indonesian manufacturing firms, traditional financial indicators are not sufficient to reflect market value. Investors tend to give greater consideration to other factors such as long-term business strategies, corporate governance quality, and growth prospects. This research contributes to the theoretical development of financial management literature and provides practical insights for company management and policymakers in designing sustainable financial strategies.